Cartilage-Repair Innovation at a Standstill: Methodologic and Regulatory Pathways to Breaking Free. (3rd August 2016) - Lyman, Stephen; Nakamura, Norimasa; Cole, Brian J.; Erggelet, Christoph; Gomoll, Andreas H.; Farr, Jack
Abstract : Abstract: Articular cartilage defects strongly predispose patients to developing early joint degeneration and osteoarthritis, but for more than 15 years, no new cartilage-repair technologies that we know of have been approved by the U.S. Food and Drug Administration. Many studies examining novel approaches to cartilage repair, including cell, tissue, or matrix-based techniques, have shown great promise, but completing randomized controlled trials (RCTs) to establish safety and efficacy has been challenging, providing a major barrier to bringing these innovations into clinical use. In this article, we review reasons that surgical innovations are not well-suited for testing through RCTs. We also discuss how analytical methods for reducing bias, such as propensity scoring, make prospective observational studies a potentially viable alternative for testing the safety and efficacy of cartilage-repair and other novel therapies, offering the real possibility of therapeutic innovation.